2016
DOI: 10.1016/j.seizure.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levetiracetam monotherapy on sperm parameters and sex hormones: Data from newly diagnosed patients with epilepsy

Abstract: Our findings confirm that LEV treatment of newly diagnosed epilepsy patients decreases sperm parameters without altering sex hormone levels. Our results may guide the choice of anti-epileptic drug treatment among men with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
5
10
0
1
Order By: Relevance
“…Post-treatment re-evaluation point was determined if 8 weeks have passed after the last seizure attacks, and if seizures occurred, we waited for another 8 weeks [2], that is, to exclude the effect of epileptic discharges on sex hormones [7].…”
Section: Laboratory Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-treatment re-evaluation point was determined if 8 weeks have passed after the last seizure attacks, and if seizures occurred, we waited for another 8 weeks [2], that is, to exclude the effect of epileptic discharges on sex hormones [7].…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Epilepsy is a chronic neurological disorder characterized by recurrent epileptic attacks, and researches have reported that the relationship between epilepsy and the reproductive dysfunction is not yet completely understood [1]. Seizures are linked with sexual dysfunction as part of the disease pathophysiology in these patients [2]. Through epileptic discharge, the hypothalamus receives signals from the hippocampus, amygdala, and cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total serum testosterone levels may be low or may not change, and therefore serum monitoring of testosterone levels for testosterone dosing should be performed, measuring free levels in transmen who take an EI‐AED. Although levetiracetam can affect sperm parameters, testosterone levels are not lowered and may be increased …”
Section: Epilepsy‐specific Considerationsmentioning
confidence: 99%
“…Although levetiracetam can affect sperm parameters, testosterone levels are not lowered and may be increased. 20,21 With the cessation of menstruation, transmen who had catamenial exacerbations of seizure frequency may experience an improvement in seizure control. Testosterone and androgens have primarily anticonvulsant effects; however, because testosterone is metabolized to 17-b-estradiol (with proconvulsant activity), the effects are more mixed.…”
Section: Transmen (Female-to-male [Ftm] Transgender Persons)mentioning
confidence: 99%